Institutions and public interest: public communication processes as instituting strategy - Carnielli, Fiorenza Zandonade (Organicom, 2017)
This article considers the processes of public communication provided by the institutions, presenting a proposal for addressing the communication centered on the normative, factual and strategic perspectives. Therefore, it develops the concepts of institution, public interest, public communication, organizational communication and strategy, emphasizing communication as an instituting strategy. The three perspectives are valid to look at institutions and understand how they articulate matters of public interest and are, therefore, subjects of public communication.